Intraocular Lens Power Calculation in Silicone Oil Filled Eye IOL Master versus A-MODE Acoustic Biometry - Tehmina Jahangir, Haroon Tayyab, Muhammad Ali Haider (Pakistan Journal of Ophthalmology, 2017)
Purpose: To compare accuracy of intraocular lens (IOL) master and A-mode acoustic biometry in patients undergoing phacoemulsification with intraocular lens implant and removal of silicone oil. Study Design: Prospective non randomized case series. Place and Duration of Study: Al-Ehsan Eye Hospital Lahore / Jinnah Hospital, Lahore. Material and Methods: This study was conducted on 30 patients with cataract and history of silicone oil in that eye as a consequence of previous vitreo-retinal surgery. Pre and post operative axial length (AXL) measurements were made using IOL master and conventional A-mode acoustic biometry. Accuracy and reliability of these techniques were compared by comparing post operative axial lengths and refractive errors. Results: Mean AXL measured with IOL master preoperatively was 23.62+/-0.36 mm. Readings noted by IOL master one month after SO removal showed a mean of 23.58+/-0.29 mm. There was no statistically significant difference (p-value 0.463). The pre and post operative AXL measured by conventional acoustic A-scan showed statistically significant difference (p-value 0.004). Preoperative AXL was 23.34+/-0.58 mm and post operative AXL was 23.97+/-0.71 mm. Post operative refractive error in IOL master group was 0.70+/-0.32 diopter sphere (DS) whereas that of acoustic A scan group was 1.55+/-0.98 DS. This difference was statistically significant (p-value 0.038) at eight weeks interval. Conclusion: IOL master is superior and more accurate for calculating AXL and post operative refractive error in SO filled eyes when compared to A-mode acoustic biometry. Keywords: IOL Master, silicone oil, axial length, phacoemulsification.